Diversity, distribution, and habitat preferences of Selaginella in Java Island, Indonesia - AHMAD DWI SETYAWAN; SUTARNO SUTARNO; SUGIYARTO SUGIYARTO; SUNARTO SUNARTO; GILANG DWI NUGROHO; MUHAMMAD NUR SULTON (Society for Indonesian Biodiversity, 2026)
Abstract. Setyawan AD, Sutarno, Sugiyarto, Sunarto, Nugroho GD, Sulton MN. 2026. Diversity, distribution, and habitat preferences of Selaginella in Java Island, Indonesia. Biodiversitas 27 (4): d270442. https://doi.org/10.13057/biodiv/d270442. Selaginella (spike mosses) is an ancient lineage of vascular plants with broad ecological adaptability, yet comprehensive ecological assessments remain limited in many tropical regions. This study investigated the diversity, distribution, and habitat preferences of Selaginella across Java Island, Indonesia, along a broad elevational gradient. Field surveys and herbarium records collected between 2007 and 2021 yielded 1,962 occurrence records, comprising 1,362 field collections and 600 herbarium specimens from BO and GBIF. Species occurrences were classified into five elevational zones: colline (0-650 m), submontane (650-1,500 m), montane (1,500-2,400 m), subalpine (2,400-3,000 m), and alpine (>3,000 m). Species diversity indices, Indicator Value Analysis (IndVal), Paired Difference Index (PDI), bipartite networks, and habitat-association analyses were used to evaluate ecological patterns. A total of 21 Selaginella species and one unidentified taxon were recorded. Species richness was highest across the colline-montane zones (0-2,400 m asl), with the greatest concentration of species occurring in the submontane zone, where diversity also reached its highest value (H′ = 2.35). Dominant species included Selaginella plana (404 individuals), Selaginella ciliaris (387), Selaginella ornata (214), and Selaginella willdenowii (205), whereas several species exhibited restricted distributions and narrow habitat preferences. Community composition differed significantly among elevational zones (p<0.05), and indicator-species analyses identified distinct habitat associations, particularly within submontane environments. These findings underscore the influence of elevation on Selaginella distribution and highlight the vulnerability of lowland and highland species to threats such as climate warming and habitat fragmentation. Conservation efforts should adopt an elevation-based strategy, emphasizing the protection of humid lowland habitats and maintaining altitudinal corridors in mountainous regions to accommodate climate-driven shifts. Safeguarding Selaginella diversity is essential for preserving the ecological integrity of tropical forest ecosystems in Southeast Asia.